RESTING HEART RATE AS A BIOMARKER OF BIOLOGICAL AGING: A REVIEW AND SYNTHESIS - Szymon Chmiela,; Gabriela Kamińska,; Natalia Bołtralik,; Julia Dzięcioł,; Zuzanna Banaś,; Kinga Dzioba,; Paulina Kisielewska,; Weronika Dmoch,; Julia Sawicka,; Arkadiusz Moskwa, (International Journal of Innovative Technologies in Social Science, 2025)
Research objectives: The objective of this study was to synthesise evidence on resting heart rate (RHR) and heart rate variability (HRV) as biomarkers of biological aging, with a focus on their relationships to multisystem physiological decline across cardiovascular, metabolic, autonomic, and inflammatory domains.Methods: A structured literature search was conducted. Included publications comprised population-based cohorts, mechanistic studies, biomarker analyses, and autonomic assessments evaluating associations between RHR, HRV, biological aging markers, morbidity, and mortality.Key findings: Elevated RHR consistently aligned with signatures of accelerated aging, including adverse cardiometabolic profiles, reduced autonomic flexibility, and increased inflammatory activation. Higher RHR was associated with older brain age, diminished functional resilience, and biomarker patterns characteristic of inflammaging, such as heightened interleukin-6 and tumour necrosis factor-α. Lower RHR corresponded to slower biological aging trajectories. HRV analyses complemented these findings, linking reduced parasympathetic activity and lower variability with diminished physiological adaptability and greater aging burden.Conclusions: RHR emerges as a robust, multidimensional biomarker that integrates signals of cumulative physiological decline and reliably identifies individuals exhibiting accelerated biological aging. Its consistent associations with molecular, functional, and clinical indicators of aging highlight its value as a practical, noninvasive tool for assessing multisystem health status.